شكر المنة في نصر السنة - المكني, احمد بن محمد (1700)
Polemics against the Ibādīyah by a muftī of Tripoli, comprising an introduction, four chapters (bāb), and a conclusion. The end of the latter is missing.
Keywords: Manuscrits -- Princeton; Polémique

رسالة بعض حوادث جربة و أحوالها - الحيلاتي, سليمان بن أحمد (1774)
Keywords: Ḥīlātī al-Ğarbī, Sulaymān ibn Aḥmad al- (16..-1688)

K. al-Tawḥīd fī Maʿrifat Allāh wa-mā yataʿallaqu bihā - Fazārī, ʿAbd Allāh ibn Yazīd (1776)
Keywords: Fazārī, ʿAbd Allāh ibn Yazīd al-; Foi -- Traité -- 8e siècle; Hintati, mosquée al- (Tunis)

al-Radd ʿalà b. ʿUmayr - Fazārī, ʿAbd Allāh ibn Yazīd (1776)
Keywords: Fazārī, ʿAbd Allāh ibn Yazīd al-; Foi -- Traité -- 8e siècle; Hintati, mosquée al- (Tunis)